Performance of Staff Administrative Services in The Regional Personnel Agency South Kalimantan Province - Frendy Arifin (LAFADZ JAYA Publisher, 2023)
This study aims to analyze the performance of personnel administration services at the South Kalimantan Provincial Civil Service Agency and what factors hinder its implementation. The research method used in this study is a qualitative method with a descriptive approach. Technical data collection is done by observation, interviews and documentation. Technical analysis of data is done by reducing data, presenting data and drawing conclusions. Checking the validity of the data was carried out using data triangulation techniques.The results of the study show that the quality of the performance of personnel administration services at the South Kalimantan Provincial Civil Service Agency is generally good where services are provided according to SOPs, carry out procedures, there are no extortion by employees, then civil servants who those given services are also satisfied, as well as the files needed by civil servants too not too long to get, it's just that there are some delays but can still be overcome. This is caused by several things, including the lack of human resources and inadequate infrastructure at the South Kalimantan Provincial Civil Service Agency.From this research, the authors suggest to the Head of the South Kalimantan Provincial Civil Service Agency to apply the rules and always evaluate the performance of personnel administration services carried out by BKD employees.